Method for preparing silicon dioxide aerogel based on waste clay bricks
By using waste clay bricks as silicon source, combined with acid and alkali combined treatment and subsequent treatment steps, a silica aerogel with excellent performance was successfully prepared, solving the problems of high raw materials, serious environmental pollution and complex preparation of the preparative technology, and achieving efficient, economical and environmentally friendly silica aerogel preparation.
Patent Information
- Application Number
- CN202510156722.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, when preparing silica aerogels, the raw materials are costly, the environmental pollution is severe, the preparation process is complex and the energy consumption is high, and there is a lack of precedent for the use of waste clay bricks as silicon source.
Use discarded clay bricks as the silicon source, and extract the inorganic silicon source through acid-base combined treatment method to prepare a silica aerogel with excellent performance. The method includes the steps of crushing waste clay bricks, alkali treatment, acid treatment, sodium ion removal, gel aging, alcoholization, hydrophobic modification and atmospheric pressure drying.
The disposal amount of waste clay bricks is increased, the environmental pollution of construction waste is reduced, the preparation cost of silica aerogel is reduced, and a more economical choice is provided for large-scale production. The prepared silica aerogel has good grid structure, high specific surface area and high temperature resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of recycling waste clay bricks, and in particular to a method for preparing silicon dioxide aerogel based on waste clay bricks. Background Art
[0002] In recent years, the state has encouraged the construction industry to use industrial waste residues, slag, silica fume, etc. as raw materials for the production of building materials. On the one hand, it has reduced carbon emissions to reduce environmental pollution caused by solid waste, and on the other hand, it has achieved high-value utilization of solid waste. At present, the annual output of construction waste in my country has reached billions of tons, of which waste bricks and stones and waste concrete account for about 40% respectively, and waste clay bricks account for more than 50% of waste bricks and stones. The recycling of waste clay bricks mainly includes: using waste clay bricks as coarse aggregates for concrete, using waste clay bricks as adsorption materials, etc., but the annual comprehensive disposal volume is still less than 50% of the annual output, and the disposal volume of waste clay bricks needs to be further increased.
[0003] The unique continuous grid structure, nanoporous and high specific surface area of silica aerogel make it have the characteristics of low density, high temperature resistance, strong adsorption and stable physical and chemical properties. This makes silica aerogel show great application potential in the fields of adsorption separation, thermal insulation and heat preservation. In recent years, the preparation method of silica aerogel has been continuously improved, but there are still some problems in commercial and large-scale production. In the preparation process, commercial silica aerogel mostly uses organic silicon source as a precursor. Not only is the raw material price high, but it is also harmful to the environment. After the widely used MTMS and MTES are completely hydrolyzed, only part of Si-OH can undergo polycondensation reaction. The prepared silica aerogel has poor structural integrity and performance stability. In addition, some of them usually need to go through high temperature and high pressure processes such as sol-gel method and supercritical drying, making the preparation process of silica aerogel extremely complicated and energy-intensive. In addition, the existing technology also has the technology of preparing silica aerogel using fly ash, water glass, etc., but there is no precedent for using waste clay bricks as silicon source to prepare silica aerogel. Summary of the invention
[0004] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to provide a method for preparing silica aerogel based on waste clay bricks. The method uses waste clay bricks from construction waste as a silicon source, effectively extracts inorganic silicon sources from waste clay bricks to prepare silica aerogel, increases the disposal volume of waste clay bricks, reduces the pollution of construction waste to the environment, and reduces the preparation cost of silica aerogel, providing a more economical option for large-scale production.
[0005] The technical solution adopted by the present invention to solve the technical problem is: In a first aspect, the present invention provides a method for preparing silica aerogel based on waste clay bricks, the method comprising the following steps: Step 1: clean the surface of the waste clay bricks, and then crush and screen them to obtain waste clay brick particles with a particle size of 80-150 μm; Step 2, preparing a NaOH solution with a mass fraction of 20%-30% and a dilute sulfuric acid solution with a concentration of 2-3 mol / L, mixing n-hexane, trimethylchlorosilane and anhydrous ethanol at a mass ratio of trimethylchlorosilane to anhydrous ethanol of 2:1-2.2:1 and a mass ratio of n-hexane to trimethylchlorosilane of 1.5:1-6:1 to obtain a hydrophobic modified liquid; Step 3: according to the ratio of adding 5300-5400g of the NaOH solution to every 1kg of the waste clay brick, the waste clay brick obtained in step 1 is mixed with the NaOH solution and stirred evenly, and placed in a constant temperature box, the temperature of the constant temperature box is 100-150°C, and the constant temperature time is 2-5h. During this process, the oxides of certain metal elements and the oxides of Si element in the waste clay brick react with the NaOH solution, and the oxides of certain metal elements do not react with the NaOH solution. In the mixture after the reaction of the waste clay brick and the NaOH solution, the oxides of the metal elements that do not react with the NaOH solution exist in the form of precipitation; the alkali treatment reaction equation is: SiO2+2NaOH→Na2SiO3+H2O Al2O3+2NaOH→2NaAlO2+H2O CaO+H2O→Ca(OH)2↓ After the alkali treatment reaction is completed, the reaction solution is obtained, filtered, and the filter cake is discarded to obtain a filtrate, the main components of which are sodium silicate, sodium metaaluminate, and sodium hydroxide; According to the ratio of adding 6700-10000g of the dilute sulfuric acid solution to every 1kg of waste clay bricks, the dilute sulfuric acid solution is slowly added to the filtrate, mixed and stirred evenly, and allowed to react for 2-4 hours. During this process, sodium silicate and sodium aluminate react with sulfuric acid, while sodium sulfate does not react with sulfuric acid. The acid treatment reaction equation is: Na2SiO3+H2SO4→H2SiO3↓+Na2SO4 2NaAlO2+H2SO4+2H2O→2Al(OH)3↓+Na2SO4 2Al(OH)3 +3H2SO4→Al2(SO4)3+6H2O Among them, silicic acid is precipitated in the form of silica gel, filtered, and the filtrate is discarded. The filter cake is mainly composed of H2SiO3, which is repeatedly washed 5-10 times to obtain a gel; Step 4, the sol obtained in step 3 is allowed to stand at room temperature for 2 days to 10 days to form a gel; then, sodium ion removal treatment, gel aging treatment, gel alcoholization treatment, hydrophobic modification treatment and normal pressure drying treatment are performed to obtain a silica aerogel; The gel aging treatment process is: placing the gel after the sodium ions are removed in water for aging for 1d-4d; The gel alcoholization treatment process is: placing the aged gel in an ethanol solution, replacing and alcoholizing with 0.5-2L of ethanol solution per 1Kg of gel, ensuring that the ethanol solution can cover the top of the gel, and standing for 12-72h; The hydrophobic modification process is: at room temperature, the gel is alcoholized and placed in the hydrophobic modification solution for hydrophobic modification; then it is immersed in n-hexane for n-hexane replacement to obtain the hydrophobically modified gel.
[0006] Furthermore, in the n-hexane replacement, 0.5-2 L of n-hexane is used for every 1 kg of gel, and the gel treated with the hydrophobic modification liquid is placed in n-hexane at room temperature for replacement for 12-48 hours.
[0007] Furthermore, the sodium ion removal process is as follows: the gel is rinsed 3-5 times with deionized water, each time for 4-10 minutes, and the sodium + The water-soluble property and the carrying capacity of flowing water remove the Na in the gel pores. + .
[0008] Furthermore, the atmospheric pressure drying process is: after the hydrophobic modification treatment, the gel is allowed to stand at room temperature for 12-48 hours, and then continued to stand at room temperature for 1 day-10 days; or after standing at room temperature for 12-48 hours, it is placed in a constant temperature drying box at 40°C-120°C and kept at the constant temperature for 20-90 minutes.
[0009] Furthermore, the particle size of the waste clay brick particles is 80-125 μm; the time of the gel alcoholization treatment is 48-72 hours, the ethanol solution is an aqueous alcohol solution, and the ethanol content is 40%-100wt%; the time of the gel aging treatment is 3-4 days.
[0010] Furthermore, the SiO2 mass content in the waste clay bricks is ≥60%, and the Al2O3 mass content is ≤20%.
[0011] Furthermore, the contents of SiO2, Al2O3, Fe2O3, CaO and MgO in the waste clay bricks are 69.93%, 15.57%, 4.64%, 4.31% and 2.08%, respectively.
[0012] The present invention also protects the silica aerogel prepared based on waste clay bricks obtained by the above method.
[0013] Furthermore, the tap density of the silica aerogel is not greater than 0.2 g / cm 3 The thermal conductivity is not greater than 0.25 W / (m·K), and the specific surface area is not less than 700 m 2 / g.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention achieves the purpose of high-value utilization of waste clay bricks, uses waste clay bricks, which are construction waste and would otherwise pollute the environment, as raw materials for preparing silica aerogels, extracts inorganic silicon from the waste clay bricks as a silicon source, and successfully prepares silica aerogels with excellent performance.
[0015] When using waste clay bricks as a silicon source to prepare silica aerogel, sodium ions will remain in the gel pores during the acid-base combined treatment process, which will produce an alkaline dissolution effect on the aerogel and increase the density of the aerogel; on the other hand, clustered sodium ions will block the pores; both will jointly lead to an increase in the thermal conductivity of the aerogel, hinder the hydrophobic modification liquid from entering the interior of the aerogel, reduce the contact area between the hydroxyl groups on the surface of the aerogel and the hydrophobic modification liquid, and prevent the hydroxyl groups from being replaced by other hydrophobic groups. During the drying step, the aerogel structure will be destroyed, the aerogel porosity will be reduced, the thermal conductivity of the aerogel will be increased, the aerogel density will be increased, and the performance of the aerogel will be reduced. The method of the present invention adds the use of a deionized water washing method to remove multiple cations (such as Na + , K + , Ca 2+ Compared with the cation exchange resin method, it has lower cost, reduces the consumption of chemical reagents, simplifies the operation steps, and lays the foundation for industrial production. The deionized water washing method is used to reduce the sodium ion content of the gel, reduce the effect of sodium ion residues blocking the aerogel pores, reduce the effect of sodium ions on thermal conductivity, facilitate the subsequent immersion of hydrophobic modification liquid and the replacement of hydroxyl groups, and simplify the operation and reduce costs.
[0016] The present invention adds a gel alcoholization process, and anhydrous ethanol is added to the hydrophobic modification liquid. The ethanol is used as a proton source to promote the hydrolysis of TMCS, accelerate the hydrolysis reaction, generate silanol (Si-OH), and further condense to form a dense siloxane (Si-O-Si) network. The hydrophobic layer is more uniform, has strong adhesion, and has a larger contact angle. The structure will not collapse when dried at room temperature and pressure, and the energy consumption is low, which saves costs.
[0017] The method of the present invention improves the composition formula of the hydrophobic modification liquid, controls the acid-base treatment process, and the subsequent treatment process of the gel for waste clay bricks, so that high-performance silica aerogel can be prepared without causing environmental pollution and at a low cost, which is a significant improvement. DETAILED DESCRIPTION
[0018] The present invention is further explained below in conjunction with embodiments, but this is not intended to limit the scope of protection of the present application.
[0019] Clay bricks are mainly used in the construction of houses with brick-concrete structures and as shaped refractory materials and unshaped refractory materials, such as blast furnace refractory materials. The main components are SiO2, Al2O3, Fe2O3 and a small amount of metal oxides. The present invention uses waste clay bricks as precursors to prepare silica aerogels. The prepared silica aerogels have good grid structures, high specific surface areas and high temperature resistance. Extracting silicon sources from waste clay bricks is easy to operate, simple to react, and cheap in raw materials.
[0020] Embodiment 1: The raw materials and properties used in this example are as follows: (1) Waste clay bricks: Silicate products with a certain strength formed by cooling clay raw materials after high-temperature sintering. Clay bricks are made of clay minerals and undergo phase transformation under high-temperature sintering to form products with a certain mechanical strength. The contents of SiO2, Al2O3, Fe2O3, CaO, and MgO in clay bricks are 69.93%, 15.57%, 4.64%, 4.31%, and 2.08%, respectively; The role of waste clay bricks: as a precursor for the preparation of silica aerogel, the silicon element in blast furnace slag is extracted by acid-base combined treatment and used as a raw material for the preparation of silica aerogel; (2) NaOH, density is 2.130 g / cm 3 , NaOH flake particles with a purity of 98%; (3) Concentrated sulfuric acid of 98%; (4) Water: tap water or deionized water.
[0021] (5) Anhydrous ethanol, chemical formula C2H5OH, molecular weight 46.08, density 0.7893 (20°C); (6) n-Hexane, chemical formula: C6H 14 , molecular weight 86.175, density 0.66 g / cm 3 (25℃); (7) Trimethylchlorosilane, chemical formula C3H9ClSi, molecular weight 102.64, density 0.854 g / cm 3 (25℃); The preparation process is: Step 1: clean the surface of the waste clay bricks by high-pressure water washing to reduce impurities adsorbed on the surface of the clay bricks and prevent the impurities from reacting with the NaOH solution, and then crush and screen to obtain waste clay brick particles with a particle size of 80-150 μm; Step 2, preparing a NaOH solution with a mass fraction of 20%-30% and a dilute sulfuric acid solution with a concentration of 2-3 mol / L, mixing n-hexane, trimethylchlorosilane and anhydrous ethanol at a mass ratio of trimethylchlorosilane to anhydrous ethanol of 2:1-2.2:1 and a mass ratio of n-hexane to trimethylchlorosilane of 1.5:1-6:1 to obtain a hydrophobic modified liquid; (1) Mixing water and NaOH flake particles to obtain a NaOH solution (solution A) with a mass fraction of 20% to 30%, preferably 20%; (2) mixing n-hexane, trimethylchlorosilane and anhydrous ethanol at a mass ratio of trimethylchlorosilane to anhydrous ethanol of 2:1 to 2.2:1 and a mass ratio of n-hexane to trimethylchlorosilane of 1.5:1 to 6:1, preferably 3:1 to 4:1, to obtain a hydrophobic modified solution (solution B); (3) Mixing water and 98% concentrated sulfuric acid to obtain dilute sulfuric acid with a concentration of 2-3 mol / L (solution C), preferably 2 mol / L; (4) Anhydrous ethanol is mixed with water to obtain an ethanol solution having an ethanol mass fraction of 40% to 100%, preferably 50% to 80wt% (solution D).
[0022] Step 3, according to the ratio of adding 5300-5400g of the NaOH solution per 1kg of waste clay brick, the waste clay brick obtained in step 1 is mixed with the NaOH solution and stirred evenly, and placed in a constant temperature box, the temperature of the constant temperature box is 100-150°C, and the constant temperature time is 2-5h (preferably the constant temperature of the constant temperature box is 120-125°C, and the constant temperature time is 2-4 hours). During this process, oxides of certain metal elements (Ca, Al, etc.) and oxides of Si elements in the waste clay brick react with the NaOH solution, and oxides of certain metal elements (Fe and Mg, etc.) do not react with the NaOH solution. In the mixture after the reaction of the waste clay brick and the NaOH solution, the oxides of the metal elements that do not react with the NaOH solution exist in the form of precipitation; the alkali treatment reaction equation is: SiO2+2NaOH→Na2SiO3+H2O Al2O3+2NaOH→2NaAlO2+H2O CaO+H2O→Ca(OH)2↓ After the alkali treatment reaction is completed, the reaction solution is obtained, filtered, and the filter cake is discarded to obtain a filtrate, the main components of which are sodium silicate, sodium metaaluminate, and sodium hydroxide; According to the ratio of adding 6700-10000g of the dilute sulfuric acid solution to every 1kg of waste clay bricks, the dilute sulfuric acid solution is slowly added to the filtrate, mixed and stirred evenly, and allowed to react for 2-4 hours, preferably 3-4 hours. During this process, sodium silicate and sodium aluminate react with sulfuric acid, while sodium sulfate does not react with sulfuric acid. The acid treatment reaction equation is: Na2SiO3+H2SO4→H2SiO3↓+Na2SO4 2NaAlO2+H2SO4+2H2O→2Al(OH)3↓+Na2SO4 2Al(OH)3 +3H2SO4→Al2(SO4)3+6H2O wherein silicic acid is precipitated in the form of silica gel, filtered, and the filtrate is discarded, the filter cake is mainly composed of H2SiO3, and is repeatedly washed 5-10 times, preferably 8-10 times, to wash away impurities on the surface of the silica gel to obtain a gel; Step 4, the sol obtained in step 3 is allowed to stand at room temperature for 2d-10d (preferably 6-10d) to form a gel; then, sodium ion removal treatment, gel aging treatment, gel alcoholization treatment, hydrophobic modification treatment and normal pressure drying treatment are performed to obtain silica aerogel.
[0023] The gel aging treatment process is: placing the gel after the sodium ions are removed in water and aging for 1d-4d, preferably 3-4d; The gel alcoholization treatment process is: placing the aged gel in an ethanol solution, replacing and alcoholizing with 0.5-2L of ethanol solution per 1Kg of gel, ensuring that the ethanol solution can cover the top of the gel, and standing for 12-72h, preferably 48-72h; The hydrophobic modification process is as follows: at room temperature, the gel is alcoholized and then placed in the hydrophobic modification liquid for hydrophobic modification for 12 hours. During the modification process, the modification liquid is shaken every 4 hours to ensure that the gel is fully modified by the modification liquid; then it is immersed in n-hexane for 12-48 hours for n-hexane replacement, and 0.5-2L of n-hexane is replaced for every 1Kg of gel to further reduce the volume shrinkage during drying, so as to obtain the hydrophobically modified gel.
[0024] The sodium ion removal process is as follows: the gel is rinsed with deionized water for 3-5 times, preferably 4-5 times, each time for about 4-10 minutes, and the sodium + The water-soluble property and the carrying capacity of flowing water remove the Na in the gel pores. + , improving the performance of silica aerogel.
[0025] The normal pressure drying process is: the hydrophobically modified gel is allowed to stand at room temperature for 12-48 hours, and then allowed to stand at room temperature for 1 day-10 days; or allowed to stand at room temperature for 12-48 hours, and then placed in a 40°C-120°C constant temperature drying oven, and kept at the constant temperature for 20-90 minutes, preferably 60-90 minutes.
[0026] Embodiment 2: (1) Weigh the waste clay bricks, wash them and crush them into waste clay bricks with a particle size of 90-110 μm, and weigh NaOH, sulfuric acid, anhydrous ethanol, n-hexane, trimethylsilyl chloride and water in proportion; (2) Mixing water and NaOH flake particles in proportion to obtain a NaOH solution with a mass fraction of 20% (solution A); (3) n-hexane, trimethylchlorosilane and anhydrous ethanol are mixed at a mass ratio of trimethylchlorosilane to anhydrous ethanol of 2:1 and a mass ratio of n-hexane to trimethylchlorosilane of 3:1 to obtain a hydrophobic modified solution (solution B); (4) Mix water and 98% concentrated sulfuric acid in proportion to obtain dilute sulfuric acid with a concentration of 2 mol / L (solution C); (5) Mixing anhydrous ethanol and water in proportion to obtain an ethanol solution with an ethanol mass fraction of 60% (solution D); (6) Extracting silicon sources from waste clay bricks; According to the ratio of adding 5400g "Solution A" to every 1kg of waste clay brick, add "Solution A" to the waste clay brick, mix and stir, place in a thermostat, temperature 120℃, react for 3 hours. After the alkali treatment reaction is completed, the reacted solution is obtained, filtered, the filter cake is discarded, and the filtrate is obtained. According to the ratio of adding 10000g "Solution C" to every 1kg of waste clay brick, "Solution C" is slowly added to the filtrate, mixed and stirred, and allowed to react for 3 hours. Filter, discard the filtrate, the main component of the filter cake is H2SiO3 gel, wash 6 times, 5 minutes each time, to wash away impurities on the surface of silica gel.
[0027] (7) Sol-gel The sol was allowed to stand at room temperature for 8 days to form a gel; (8) Removal of sodium ions Using the deionized water washing method, the gel was rinsed with deionized water for 5 times, 10 min each time, with an interval of 20 min; (9) Gel aging The gel was placed in water and aged for 3 days to obtain an aged gel; (10) Gel aging At room temperature, place the aged gel in "Solution D" and replace it with 1L of ethanol solution for every 1Kg of gel. Choose a suitable container to ensure that "Solution D" can cover the top of the gel and let it stand for 72 hours. (11) Hydrophobic modification At room temperature, place the wet gel in "Solution B" and perform hydrophobic modification for 12 hours at room temperature. During the modification process, shake the modification solution every 4 hours; Afterwards, the gel was placed in n-hexane for 30 h at room temperature, and 1 kg of gel was replaced with 1 L of n-hexane solution to further reduce volume shrinkage during drying; (12) Drying at normal pressure The gel was allowed to stand at room temperature for 24 hours and then continued to stand at room temperature for 6 days to obtain silica aerogel.
[0028] Embodiment 3: The steps of this embodiment are the same as those of Embodiment 2, except that the mass ratio of trimethylsilyl chloride to anhydrous ethanol is 2.2:1, and the mass ratio of n-hexane to trimethylsilyl chloride is 5:1.
[0029] Embodiment 4: The steps of this embodiment are the same as those of embodiment 3, except that solution D is an 80 wt % ethanol solution.
[0030] Embodiment 5: The steps of this embodiment are the same as those of embodiment 2, the mass ratio of trimethylchlorosilane to anhydrous ethanol is 2:1, the mass ratio of n-hexane to trimethylchlorosilane is 3:1, and solution D is a 60 wt% ethanol solution. The difference is that solution C is 3 mol / L dilute sulfuric acid.
[0031] Embodiment 6: The steps of this embodiment are the same as those of Embodiment 2, except that the mass ratio of trimethylchlorosilane to anhydrous ethanol is 2:1, the mass ratio of n-hexane to trimethylchlorosilane is 6:1, solution C is 3 mol / L dilute sulfuric acid, and solution D is 80 wt % ethanol solution.
[0032] Embodiment 7: The steps of this embodiment are the same as those of embodiment 2, except that solution C is 3 mol / L dilute sulfuric acid, and solution D is 80 wt % ethanol solution.
[0033] Comparative Example 1: The steps in this comparative example are the same as those in Example 2, except that the mass ratio of trimethylchlorosilane to anhydrous ethanol is 1:1, and the mass ratio of n-hexane to trimethylchlorosilane is 1:1.
[0034] Comparative Example 2: The steps in this comparative example are the same as those in Example 2, except that the particle size of the crushed waste clay bricks is 180-250 μm, the mass ratio of trimethylchlorosilane to anhydrous ethanol is 1:1, and the mass ratio of n-hexane to trimethylchlorosilane is 5:1.
[0035] Comparative Example 3: The steps in this comparative example are the same as those in comparative example 2, except that the particle size of the waste clay bricks is 180-250 μm, the mass ratio of trimethylchlorosilane to anhydrous ethanol is 1:1, and the mass ratio of n-hexane to trimethylchlorosilane is 8:1.
[0036] Comparative Example 4: The steps in this comparative example are the same as those in Example 2, and the particle size of the crushed waste clay bricks is 90-110 μm. The difference is that hexamethylchlorosilane is used instead of trimethylchlorosilane, and n-hexane, hexamethylchlorosilane and anhydrous ethanol are mixed at a molar ratio of hexamethyldisilazane to anhydrous ethanol of 1:1 and a ratio of the volume of n-hexane to the total volume of the hexamethyldisilazane and anhydrous ethanol of 1:1.
[0037] The silica aerogels obtained in the examples and comparative examples were subjected to relevant performance tests, and the test results are shown in Table 1.
[0038]
[0039] It can be seen from the above table that the embodiments of the present invention can obtain a tap density of no more than 0.2 g / cm 3 The thermal conductivity is not greater than 0.25 W / (m·K), and the specific surface area is not less than 700 m 2 / g and other comprehensive performance of silica aerogel. The performance of the comparative silica aerogel is obviously poor. In particular, the tap density can be controlled to be no more than 0.15g / cm 3 .
[0040] The present invention successfully achieves the purpose of preparing high-performance silica aerogel from waste clay bricks. The inorganic silicon extracted from waste clay bricks is used as a precursor. The waste clay bricks contain sufficient silicon, reaching more than about 60%, and the extraction is simple. The sodium removal step is added to reduce the influence of sodium ions on the thermal conductivity, porosity and density of the aerogel, thereby improving the performance of the silica aerogel. In addition, the subsequent aging, alcoholization, hydrophobic modification and drying processes of the present invention can be carried out at room temperature, or dried in a short time (up to 90 minutes), with less energy consumption and significant cost savings.
[0041] Any matters not described in the present invention are applicable to the prior art.
Claims
1. A method for preparing silica aerogel based on waste clay bricks, characterized in that: The method comprises the following steps: Step 1: clean the surface of the waste clay bricks, and then crush and screen them to obtain waste clay brick particles with a particle size of 80-150 μm; Step 2, preparing a NaOH solution with a mass fraction of 20%-30% and a dilute sulfuric acid solution with a concentration of 2-3 mol / L, mixing n-hexane, trimethylchlorosilane and anhydrous ethanol at a mass ratio of trimethylchlorosilane to anhydrous ethanol of 2:1-2.2:1 and a mass ratio of n-hexane to trimethylchlorosilane of 1.5:1-6:1 to obtain a hydrophobic modified liquid; Step 3: according to the ratio of adding 5300-5400g of the NaOH solution to every 1kg of the waste clay brick, the waste clay brick obtained in step 1 is mixed with the NaOH solution and stirred evenly, and placed in a constant temperature box, the temperature of the constant temperature box is 100-150°C, and the constant temperature time is 2-5h. During this process, the oxides of certain metal elements and the oxides of Si element in the waste clay brick react with the NaOH solution, and the oxides of certain metal elements do not react with the NaOH solution. In the mixture after the reaction of the waste clay brick and the NaOH solution, the oxides of the metal elements that do not react with the NaOH solution exist in the form of precipitation; the alkali treatment reaction equation is: SiO2+2NaOH→Na2SiO3+H2O Al2O3+2NaOH→2NaAlO2+H2O CaO+H2O→Ca(OH)2↓ After the alkali treatment reaction is completed, the reaction solution is obtained, filtered, and the filter cake is discarded to obtain a filtrate, the main components of which are sodium silicate, sodium metaaluminate, and sodium hydroxide; According to the ratio of adding 6700-10000g of the dilute sulfuric acid solution to every 1kg of waste clay bricks, the dilute sulfuric acid solution is slowly added to the filtrate, mixed and stirred evenly, and allowed to react for 2-4 hours. During this process, sodium silicate and sodium aluminate react with sulfuric acid, while sodium sulfate does not react with sulfuric acid. The acid treatment reaction equation is: Na2SiO3+H2SO4→H2SiO3↓+Na2SO4 2NaAlO2+H2SO4+2H2O→2Al(OH)3↓+Na2SO4 2Al(OH)3 +3H2SO4→Al2(SO4)3+6H2O Among them, silicic acid is precipitated in the form of silica gel, filtered, and the filtrate is discarded. The filter cake is mainly composed of H2SiO3, which is repeatedly washed 5-10 times to obtain a gel; Step 4, the sol obtained in step 3 is allowed to stand at room temperature for 2 days to 10 days to form a gel; then, sodium ion removal treatment, gel aging treatment, gel alcoholization treatment, hydrophobic modification treatment and normal pressure drying treatment are performed to obtain a silica aerogel; The gel aging treatment process is: placing the gel after the sodium ions are removed in water for aging for 1d-4d; The gel alcoholization treatment process is: placing the aged gel in an ethanol solution, replacing and alcoholizing with 0.5-2L of ethanol solution per 1Kg of gel, ensuring that the ethanol solution can cover the top of the gel, and standing for 12-72h; The hydrophobic modification process is: at room temperature, the gel is alcoholized and placed in the hydrophobic modification solution for hydrophobic modification; then it is immersed in n-hexane for n-hexane replacement to obtain the hydrophobically modified gel.
2. The method according to claim 1, characterized in that In the n-hexane replacement, 0.5-2 L of n-hexane is used for every 1 kg of gel. The gel treated with the hydrophobic modification liquid is placed in n-hexane at room temperature for replacement for 12-48 hours.
3. The method according to claim 1, characterized in that The sodium ion removal process is as follows: the gel is rinsed 3-5 times with deionized water, each time for 4-10 minutes, and the ... + The water-soluble property and the carrying capacity of flowing water remove the Na in the gel pores. + .
4. The method according to claim 1, characterized in that The normal pressure drying process is: the hydrophobically modified gel is allowed to stand at room temperature for 12-48 hours, and then allowed to stand at room temperature for 1 day-10 days; or allowed to stand at room temperature for 12-48 hours, and then placed in a 40-120°C constant temperature drying oven for 20-90 minutes.
5. The method according to claim 1, characterized in that The particle size of the waste clay brick particles is 80-125 μm; the time of the gel alcoholization treatment is 48-72 hours, the ethanol solution is an aqueous alcohol solution, and the ethanol content is 40%-100wt%; the time of the gel aging treatment is 3-4 days.
6. The method according to claim 1, characterized in that The waste clay bricks have a SiO2 mass content of ≥60% and an Al2O3 mass content of ≤20%.
7. The method according to claim 1, characterized in that The contents of SiO2, Al2O3, Fe2O3, CaO and MgO in waste clay bricks are 69.93%, 15.57%, 4.64%, 4.31% and 2.08% respectively.
8. A silica aerogel prepared from waste clay bricks obtained by the method according to any one of claims 1 to 7.
9. The silica aerogel according to claim 8, characterized in that The tap density of the silica aerogel is no more than 0.2 g / cm 3 The thermal conductivity is not greater than 0.25 W / (m·K), and the specific surface area is not less than 700 m 2 / g.
Citation Information
Patent Citations
Method for ordinary-pressure preparation of aerosil with kaolin waste residue as raw material
CN103936017A
Method for preparing nano silicon dioxide aerogel by using waste glass
CN113264533A
Preparation method of low-carbon-emission silicon dioxide aerogel
CN118183762A
Method for preparing hydrophobic silicon dioxide aerogel from fine coal gasification slag
CN118343772A
Cited By
Method for preparing silicon dioxide aerogel powder from building solid waste micro powder and silicon dioxide aerogel powder
CN121269729A